Theoretical Investigation of an Air-Slot Mode-Size Matcher between Dielectric and MDM Plasmonic Waveguides - Rami A. Wahsheh (International Journal of Optics)
Hybrid integration of dielectric and plasmonic waveguides is necessary to reduce the propagation losses due to the metallic interactions and support of nanofabrication of plasmonic devices that deal with large data transfer. In this paper, we propose a direct yet efficient, very short air-slot coupler (ASC) of a length of 36 nm to increase the coupling efficiency between a silicon waveguide and a silver-air-silver plasmonic waveguide. Our numerical simulation results show that having the ASC at the interface makes the fabrication process much easier and ensures that light couples from a dielectric waveguide into and out of a plasmonic waveguide. The proposed coupler works over a broad frequency range achieving a coupling efficiency of 86% from a dielectric waveguide into a metal-dielectric-metal (MDM) plasmonic waveguide and 68% from a dielectric waveguide to an MDM plasmonic waveguide and back into another dielectric waveguide. In addition, we show that even if there are no high-precision fabrication techniques, light couples from a conventional dielectric waveguide (CDW) into an MDM plasmonic waveguide as long as there is an overlap between the CDW and ASC, which reduces the fabrication process tremendously. Our proposed coupler has an impact on the miniaturization of ultracompact nanoplasmonic devices.